Molecular diagnostic assays for the detection of common bacterial meningitis pathogens: a narrative review - Diallo, K; Vitalis, FF; Ibe, L; Antonio, M; Caugant, DA; du Plessis, M; Deghmane, AE; Feavers, IM; Fernandez, K; Fox, LM; Rodrigues, CMC; Ronveaux, O; et al. (Elsevier, 2021)
Bacterial meningitis is a major global cause of morbidity and mortality. Rapid identification of the aetiological agent of meningitis is essential for clinical and public health management and disease prevention given the wide range of pathogens that cause the clinical syndrome and the availability of vaccines that protect against some, but not all, of these. Since microbiological culture is complex, slow, and often impacted by prior antimicrobial treatment of the patient, molecular diagnostic assays have been developed for bacterial detection. Distinguishing between meningitis caused by Neisseria meningitidis (meningococcus), Streptococcus pneumoniae (pneumococcus), Haemophilus influenzae, and Streptococcus agalactiae and identifying their polysaccharide capsules is especially important. Here, we review methods used in the identification of these bacteria, providing an up-to-date account of available assays, allowing clinicians and diagnostic laboratories to make informed decisions about which assays to use.